Transfer and heating mechanisms of a curry puff vending machine - Mohd Ali, Muhamad Khalid; Zainul Azlan, Norsinnira; Ali, Muhammad Aminuddin Anwar (Asian Research Publishing Network (ARPN), 2016)
This paper focuses on the design and development of the transfer and heating mechanisms of a curry puff vending machine. The vending machine contains frozen pre-cooked curry puffs that are packed in containers and require heating process before being dispensed to the consumers. The transfer mechanism transfers the containers containing frozen curry puffs into the microwave by using a slider and brings it out after being heated. In the heating mechanism, the microwave’s door is opened and closed by a servo motor through a four bar linkage mechanism and the timer knob is automatically adjusted by a servo motor. The experimental results have shown that the proposed mechanisms have successfully transferred and heated the curry puff for the vending machine application. The main advantage of this system is it allows the curry puffs to be served while it is still hot and fresh to the customers at any time and thus making it tastier.